INVESTIGATION OF THE SIGNIFICANCE OF DETECTION OF THE NUCLEOCAPSID ANTIGEN OF THE HEPATITIS C VIRUS IN CHILDREN WITH CHRONIC HEPATITIS C - E. A. Leybman; L. I. Nikolaeva; G. V. Sapronov; E. I. Samokhvalov; O. B. Kovalev; V. A. Konev; V. F. Uchaikin (LLC "Diagnostics and Vaccines", 2017)
The aim of this study was to investigate the clinical and diagnostic significance of the detection of core-antigen of hepatitis C virus (HCV) in children with chronic hepatitis C (CHC). Sera of 101 patients and 24 non-infected participants were analyzed. Core-antigen was determined by chemiluminescent method using «ARCHITECT HCV Ag» (Abbott, USA). HCV RNA was detected by highly sensitive OT-PCA. The presence of liver fibrosis was established by non-invasive methods. Antibody to core-antigen was detected by ELISA using commercial test-systems. A correlation was found between concentration of core-antigen and HCV RNA, viral subtypes, ALT level, and presence of liver fibrosis. High sensitivity and specificity of the chemiluminescent method for the detection of core antigen in children with CHC was shown. For the first time three ranges of core-antigen concentrations were proposed.